A crossover pharmacokinetic study of misoprostol by the oral, sublingual and buccal routes. (3rd July 2016) - Frye, Laura J.; Byrne, Meagan E.; Winikoff, Beverly
Abstract: Objectives: The aim of the study was to compare the pharmacokinetic parameters of 800 μg oral, sublingual and buccal misoprostol in healthy non-pregnant women.Methods: This was an open-label, randomised study with a three-way crossover design. Eighteen participants were randomly assigned to treatment sequences of 800 μg oral, sublingual and buccal misoprostol administered under fasting conditions, with a 7-day washout period. Ten participants completed all routes. The primary pharmacokinetic parameters measured were the area under the plasma misoprostol acid concentration–time curve (AUC) from dosing to last quantifiable concentration (AUC0–t), the AUC from 0 to infinity (AUC0–∞) and the maximum plasma concentration (Cmax). Secondary parameters included the plasma elimination rate constant (ke ), the half-life and the mean residence time (MRT).Results: There were statistically significant differences in AUC0–∞, AUC0–t and Cmax at the p  < 0.05 level for the three routes of administration. The sublingual route achieved the highest bioavailability, and the buccal route achieved the lowest peak concentration. The oral and buccal routes had a similar AUC0–∞ and the buccal route had the highest MRT and ke . There were no differences in half-lives, and no serious adverse events were reported.Conclusions: This study shows variability in Cmax and AUC by three by-mouth routes of misoprostol administration. The dose in this study was 800 μg, which is among the highest doses seen in current guidelines. These data contribute to the understanding of efficacy and safety of different routes and could provide a basis for deciding whether certain routes are preferable for particular indications.